Modeling and Experimental Validation of a Transient Direct Expansion Heat Pump - Rousseau, ClÃ©ment; Fannou, Jean-Louis Comlan; Lamarche, Louis; Kajl, Stanislaw (Center of Biomass & Renewable Energy, Diponegoro University, 2017)
Geothermal heat pump technology is currently one of the most interesting technologies used to heat buildings. There are two designs used in the industry: geothermal heat pump using a secondary ground loop and Direct Expansion (DX) ground source heat pump. The latter is less used, possibly because less research has been carried out for the design of this kind of heat pump. In this paper, a transient model using the Comsol Multiphysic of a DX ground heat pump is presented in heating mode with R22, and a comparison with experimental results is presented with a 24-hour test. It is shown that the model was adequately validated by our experiment with only a maximum difference of 15%. Following this validation, a parametric analysis was realised on the geometry of the borehole. This study concluded that to have the best heat extraction of the ground, the pipes shank spacing need to be important without increasing the borehole diameter.Article History: Received January 16th 2017; Received in revised form May 28th 2017; Accepted June 6th 2017; Available onlineHow to Cite This Article: Rousseau, C., Fannou, J.L.C., Lamarche, L. and Kajl, S. (2017) Modeling and Experimental Validation of a Transient Direct Expansion Heat Pump. International Journal of Renewable Energy Development, 6(2), 145-155.https://doi.org/10.14710/ijred.6.2.145-155